Whole Body Vibration Triggers a Change in the Mutual Shaping State of Intestinal Microbiota and Body's Immunity - Song, Ning; Liu, Xia; Feng, Qiang; Xu, Mengchen; Lan, Xiang; Li, Meihui; Liu, Rutao; Li, Caixia; Dong, Tianyi; Wang, Deqiang; Liu, Shili (Frontiers in Bioengineering and Biotechnology, 2019)
Whole body vibration (WBV) is a non-invasive physical therapy that has recently been included in the hospital's patient rehabilitation training catalog, but its health effects have not been sufficiently studied. In the present study, to examine the possible effects of WBV on immune cell differentiation, the IFN, IL-4,−17, F4/80 and CD3,−4,−8,−11b,−11c,−19 markers were used to characterizing the cells in mouse spleen. The results showed that the CD4 and CD25 positive lymphocytes in the spleen were significantly increased in the WBV group, and the population of Treg cells was enhanced significantly in response to WBV. Since the differentiation in immune cells is usually associated with microbiota, therefore the intestinal flora was characterized in mice and human individuals. The results indicated that WBV significantly reduced the α-diversity of mouse intestinal microbiota. Moreover, the principal coordinate analysis (PCoA) results indicated that the β-diversities of both mice and human fecal microbiota increased after WBV. Analysis of the bacterial composition indicated that the contents of a variety of bacteria changed in mice upon the stimulation of vibration, such as Lactobacillus animalis in mice, and Lactobacillus paraplantarum and Lactobacillus sanfranciscensis in human. The succeeding correlation analysis revealed that some bacteria with significant content variations were correlated to the regulatory T cell differentiation in mice and physical characteristics in human. Our research will provide the basis for future non-invasive treatment of microbial and immune related diseases.